DEVELOPING CREATIVEECONOMY FOR COMMUNITY LEARNERS IN SUPPORTING TOURISM IN TEMBOK AND ABANG VILLAGE, BALI - I Ketut Sudita; Dewa Nyoman Sudana; I Nengah Suandi; Dewa Bagus Sanjaya (Universitas Pendidikan Ganesha, 2017)
Community group learners are a community group that sets an example and deserves to be given a priority in a program for strengthening and extending economy, especially in Bali province. Departing from this idea, this study was aimed (1) to produce an innovative design for handicrafs (creative economy) for community group learners which matches their existing potentialities, (2) to produce a creative economy strategy at a larger scale. The results of this study showed that the craftsmen had been able to produce various handicrafts such as laptop baggage, sokasi (bamboo basketwork used for holding rice), ballpoint stand, bamboo basket or tray for keeping offerings with a variety of designs. Community learners were able to develop product to meet the market conditions and demands and were able to develop a larger network, with the local government, universities, and businesses.